Cellulose : - Tarchevsk, I. A. (Springer-Verlag, 1991)
The monograph is written for specialists in plant physiology and biochemistry, structural chemistry of polymers, and for specialists in agriculture and in the paper und pulp industry. It is an indispensable source of information.